Получение керамических матриц на основе пирохлора Gd₂Zr₂O₇ - Шкуропатенко, В. А.; Тарасов, Р. В.; Лобач, К. В.; Степина, В. В.; Миронова, А. Г.; Одейчук, М. А. (НТУ "ХПИ", 2015)
Приведены результаты исследований твердофазного синтеза и получения плотных образцов пирохлора Gd₂Zr₂O₇. Методом горячего прессования в вакууме при Т = 1450 °С, Р = 50 МПа и времени выдержки 1 час получены керамические образцы пирохлора Gd₂Zr₂O₇ с относительной плотностью 92,5 % и пределом прочности при изгибе 58,74 МПа. Методами рентгенофазового анализа и электронной микроскопии показано, что полученный материал, в основном, представлен пирохлором Gd₂Zr₂O₇ и незначительным количеством исходных оксидов. Предоставлены рекомендации относительно использования данных исследований для разработки керамических материалов, предназначенных для иммобилизации актиноидов и РЗЭ-актиноидной фракции ВАО.

The solid-state synthesis of gadolinium zirconate pyrochlore Gd₂Zr₂O₇ and obtaining of dense samples Gd₂Zr₂O₇ are investigated. The solid-state synthesis of pyrochlore Gd₂Zr₂O₇ spent in vacuum at temperature 1450 °С within 2 hours. Research of phase structure of the synthesized pyrochlore powder has shown, that under the given conditions on the X-ray diffraction pattern together with pyrochlore lines X-ray lines of oxides initial components are observed. Сeramic samples of pyrochlore Gd₂Zr₂O₇ with relative density 92,5 % were produced by the method of hot pressing in vacuum at temperature 1450 °С, compacting pressure 50 MPa and mold-cycle time 1 hour. By methods X-ray diffraction analysis and electronic microscopy it is shown, that the received material, basically, it is presented pyrochlore Gd₂Zr₂O₇ and insignificant quantity initial oxides. Bending strength, calculated by results of tests for diametrical compression of such samples, makes 58,74 MPa. Recommendations concerning use of the given researches for development of the ceramic materials intended for immobilization of actinide elements and REE-actinide of fraction high-level radioactive waste are given.
Obtaining of ceramics matrix based on the pyrochlore Gd₂Zr₂O₇
Keywords: синтез твердофазный; отходы радиоактивные; прессование горячее; измельчение; solid-state synthesis; radioactive waste; hot pressing; milling